Humans and AI: differences, opportunities, threats Reflections around the Note Antiqua et nova - Kowalczyk, Dariusz (Chrześcijaństwo-Świat-Polityka, 2025)
The article, drawing on the Vatican document Antiqua et nova and Leo XIV’s proclamation of his intention to confront the challenge of new digital technologies, addresses the relationship between natural intelligence, notably human intelligence, and artificial intelligence. In this context, the author further discusses transhumanism and the resulting concepts of human ‘enhancement’, contrasting them with the Christian vision of the human being created in God’s image. In the central section of the text, he analyses the concepts of human, animal and artificial intelligence, emphasising the key role played by intentionality, freedom and the relational dimension in distinguishing human intelligence from AI. Using, inter alia, the distinction between noûs [contemplative mind] and mêtis [practical intelligence], the author points out that AI possesses solely functional abilities, devoid of intentionality and of reference to a sense of meaning and values. Furthermore, in light of Antiqua et nova, the author discusses the opportunities and threats associated with the use of artificial intelligence in education, medicine, economy, communication, politics, and the military, as well as the risk of technocracy and deepening inequality. The article emphasises that AI should remain a tool that serves the human being, and its development requires ethical supervision, in which Christian anthropology can be of considerable assistance.